2017
DOI: 10.1007/s10549-017-4577-x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the 8th AJCC prognostic staging system for breast cancer in a population-based setting

Abstract: The current analysis showed an improvement in the discriminatory value for the prognostic staging system compared to the anatomical staging system and endorsed its routine use in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 16 publications
4
63
0
Order By: Relevance
“…To provide more accurate prognostic information for BC patients, the novel prognostic staging system was proposed by AJCC in October 2016, in which ER, PR, Her‐2, and histological grade were incorporated into the anatomic TNM staging . To date, the validity of the prognostic staging system has been validated in some studies . Weiss et al demonstrated that the new prognostic staging had a higher Harrell concordance index(C index) and lower Akaike information criterion (AIC) value, which mean better prognostic performance than the anatomic TNM staging alone .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To provide more accurate prognostic information for BC patients, the novel prognostic staging system was proposed by AJCC in October 2016, in which ER, PR, Her‐2, and histological grade were incorporated into the anatomic TNM staging . To date, the validity of the prognostic staging system has been validated in some studies . Weiss et al demonstrated that the new prognostic staging had a higher Harrell concordance index(C index) and lower Akaike information criterion (AIC) value, which mean better prognostic performance than the anatomic TNM staging alone .…”
Section: Discussionmentioning
confidence: 99%
“…Since the novel staging system for BC was proposed by AJCC, its prognostic value and availability have been validated in BC patients . However, the prognostic staging system seems to be somewhat complex and not convenient for clinical application due to the redundant grouping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several retrospective studies were undertaken to validate the AJCC eighth edition PS and had present concrete evidence of the advantages of PS in refining stratification and prognostic information . For instance, Weis et al reviewed a total of 3,327 patients with stage I to IIIC breast cancer treated between 2007 and 2013 at MD Anderson Cancer Center and identified a total of 54,727 patients with stage I to IV breast cancer treated between 2005 and 2009 in the California Cancer Registry .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the prognostic staging system in conjunction with RS has not yet been validated in any study. The prognostic staging system has been validated in prior series, but those studies did not focus on the incorporation of RS . Moreover, few studies performed the validation and comparison among the three staging systems to determine the most useful classification criteria for patients.…”
Section: Introductionmentioning
confidence: 99%